Fabrication, Characterization, Mechanical and Combustion Properties of Bio-Briquettes Derived from Agro-Wastes of Bush Mangonut Shell and Sugarcane Bagasse - Eze, Nkechinyere Olivia; Ikelle, Ikelle; Nworie, Felix Sunday; Nworu, Jerome; Onuegbu, Theresa (Asian Journal of Energy Transformation and Conservation, 2021)
Sequel to the environmental problems associated with wastes in our environment and coupled with the need for effective waste management, this work produced briquettes from agro-wastes of bush mangonut shell (BMS) and sugarcane bagasse (SB). The agro-wastes were crushed to small particle sizes, and compressed in a screw press with compaction pressure of 13.4kPa to produce the briquettes. The metal content and morphology were determined using an Atomic Absorption Spectrometer (AAS) and Scanning Electron Microscope (SEM) respectively. Proximate analyses of the biomasses and briquettes were done using standard methods. Compressive strength and calorific values of the briquettes was determined using compressive strength testing machine and Oxygen Bomb calorimeter respectively. The AAS analyses indicated the presence of Ca (32.19mg/kg), Si (1.43mg/kg), K (0.66mg/kg), P (0.04mg/kg) in SB and Ca (22.20mg/kg), Si (2.05 mg/kg), K (1.21mg/kg), P (0.02mg/kg) for BMS. SEM analyses showed different lignocellulosic structures. The ash contents of the BMS and SB were 4.92 ± 0.05% and 4.16 ± 0.02% respectively. The calorific value of the BMS briquette was 20.9 ± 0.36 MJ/kg and 20.8 ± 0.00 MJ/kg for SB briquette. The low ash content and low concentration of metals in the biomasses presented them as suitable feedstock for bio-fuel production. The briquettes have high calorific values and good mechanical properties, and are recommended for domestic and industrial purposes. Briquetting of agro wastes is economical as it is a way of converting wastes to wealth, and at the same time providing an alternative and renewable source of energy to man.